2006
DOI: 10.1021/ac060960p
|View full text |Cite
|
Sign up to set email alerts
|

Electron Capture Dissociation as Structural Probe for Noncovalent Gas-Phase Protein Assemblies

Abstract: Electron capture dissociation (ECD) of proteins in Fourier transform ion cyclotron resonance mass spectrometry usually leads to charge reduction and backbone-bond cleavage, thereby mostly retaining labile, intramolecular noncovalent interactions. In this report, we evaluate ECD of the 84-kDa noncovalent heptameric gp31 complex and compare this with sustained off-resonance irradiation collisionally activated dissociation (SORI-CAD) of the same protein. Unexpectedly, the 21+ charge state of the gp31 oligomer exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 39 publications
2
60
0
Order By: Relevance
“…This result was in stark contrast to SORI-CAD experiments in which disassembly of two constituent molecules, Angiotensin II and ␤-CD, was a dominant process. Conservation of noncovalent interactions during ECD peptide backbone dissociation, as observed here, is consistent with well-known ECD characteristics [28][29][30][31][32][33][34]41,42,44]. In addition, a singly reduced species [A:CD+2H] •+ and its ammonia-loss counterpart [A:CD-NH 3 +2H] •+ were observed at m/z 2476.9 and 2459.6, respectively.…”
Section: Ecd Of Angiotensin Ii-ˇ-cd Complex [A:cd+2h] 2+supporting
confidence: 89%
See 1 more Smart Citation
“…This result was in stark contrast to SORI-CAD experiments in which disassembly of two constituent molecules, Angiotensin II and ␤-CD, was a dominant process. Conservation of noncovalent interactions during ECD peptide backbone dissociation, as observed here, is consistent with well-known ECD characteristics [28][29][30][31][32][33][34]41,42,44]. In addition, a singly reduced species [A:CD+2H] •+ and its ammonia-loss counterpart [A:CD-NH 3 +2H] •+ were observed at m/z 2476.9 and 2459.6, respectively.…”
Section: Ecd Of Angiotensin Ii-ˇ-cd Complex [A:cd+2h] 2+supporting
confidence: 89%
“…ECD MS has many useful characteristics, including high fragmentation efficiency and superior capability in characterizing post-translational modifications such as phosphorylation and glycosylation [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Furthermore, it has been shown that noncovalent interactions, both intramolecular and intermolecular, generally remain intact in ECD MS [28][29][30][31][32][33][34]41,42,44]. We utilized this unique property of ECD MS to study the interaction characteristics of permethylated ␤-CD-peptide complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Black-body infrared radiative dissociation [15], electron-capture dissociation [17], infrared multiphoton dissociation [14,16], and surface-induced dissociation [18,64] have all been applied to protein assemblies. Of these, the latter is notable for the large amount of energy deposited into the protein complexes in a very short time, resulting in more extensive dissociation than that in CID [65].…”
Section: Frontiers In Gas-phase Activation Of Protein Complexesmentioning
confidence: 99%
“…In these experiments, charge reduction and the subsequent transmission and detection of the resulting extremely high m/z species typically require instrument modifications [15,18]. Limited charge reduction is also typically observed as a side reaction in electron capture (ECD) and electron transfer dissociation (ETD) experiments, without instrument modification, particularly when working with intact proteins [19][20][21][22][23][24]. In addition, ECD or ETD fragments can remain bound to each other by noncovalent interactions so that they appear as chargereduced precursor ions in the spectra [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%